Foreword to Special Issue “Valorization of biomass and waste: the path for sustainability and circular economy promotion” - Jellali, Salah; Jeguirim, Mejdi (Comptes Rendus. Chimie, 2025)
Biomass and wastes are produced in huge amounts all over the world. Even if they have high potential to be valorized in various sectors including energy, agriculture, and environment, a big fraction continues to be considered as a serious burden. This situation is worsened by the global climate change due to important emission of greenhouse gases (GHGs) generated by the consumption of considerable amounts of fossil fuels and also by the mismanagement of the produced biomass and wastes. The sustainable valorization of these biomass and wastes for energy recovery, synthesis of new materials for use in industry, in agriculture, and in environment, will decrease GHG emission, boost the circular economy, and preserve the environment. The current special issue published in Comptes Rendus Chimie (CRC) reviews recent advancements in biomass and waste valorization for the promotion of circular economy and sustainability concepts.